Undergraduate instrumental analysis - Robinson, James W., 1923-2018; Frame, Eileen M. Skelly, 1953-; Frame, George M., II (CRC Press, 2014)
"Building on the success of previous editions, Undergraduate Instrumental Analysis: Seventh Edition expands and revises its coverage to provide the latest information on the newest techniques, such as cavity ringdown spectroscopy and LIBS. This book features details on XRD and its uses in materials analysis as well as additional material on surface analysis. Application chapters focus on the analysis of nanomaterials and chemical and biological warfare agents; in particular, these chapters discuss hyphenates techniques for these materials (like LCMS, GCMS, and LC-ICPMS). The text integrates experiments and problem sets, including those requiring the use of spreadsheet programs such as Excel"--Resumé vydavatele
"With Vitalsource ebook."--Z obálky
Keywords: instrumentální analýza; spektroskopie; spektrometrie; chromatografie; instrumental analysis; spectroscopy; spectrometry; chromatography; učebnice; textbooks